SUGARCANE COMPANIES’ PREFERENCES FOR CERTIFIED SUPPLIERS IN THE SUPPLY CHAIN - Oenning, Eduardo; de Oliveira, Lucas; de Melo, Fagner; Xavier, Larissa; de Medeiros, Denise Dumke (Brazilian Journal of Operations & Production Management, 2020)
Goal: The main objective of this study was to evaluate the preference structure for MSS certifications in a Brazilian supply chain. Design/methodology/approach: To form the set of attributes, five MSS were selected that certify companies in the Brazilian sugarcane supply chain, and a sample of 66 large and medium-sized companies in operation was obtained. Results: The results show that the Brazilian sugarcane companies supply chain presented a higher preference for suppliers with ISO 9001 (38.7%), ISO 22000 (19.9%), ISO 14001 (19.6%), OHSAS 18001 (13.2%) and ISO 27001 (8.6%) certification and contribute to the literature by offering new and broader insight into industrial buying behavior in the business-to-business context with respect to the adoption of MSS. Limitations of the investigation: The low number of observations may be a factor limiting the investigation. And the study is limited to sugar-alcohol companies in Brazil. Practical implications: Companies within the supply chain still prefer the traditional certifications, even when the market is saturated with such certifications. These results help better explain industrial behavior and illuminate the relationships that companies develop within the supply chain, that might thus be of great assistance to suppliers wishing to become part of this supply chain by identifying which MSS certifications are most valued by purchasing companies. Originality/value: The article analyzes which MSS are most important for the Brazilian companies of sugar cane and ethanol. And can be of great value to managers, suppliers, and stakeholders in this industry, as well as a model for developing countries.